THE EFFECT OF LEVERAGE, PROFITABILITY, AND SIZE OF THE COMPANY ON PROFIT MANAGEMENT IN MINING SECTOR COMPANY IN 2014-2017 (International Journal of Psychosocial Rehabilitation, 2020)
The company's financial statements that describe the company's financial performance are the income statement. The income statement can help investors find out the level of profitability of the company and the value of its investment in the future. The main focus in financial reporting is information about company performance that is available by measuring earnings and its components. This study aims to determine the effect of leverage, profitability, and firm size on earnings management in mining sector companies listed on the Indonesia Stock Exchange in 2014-2017. The research method used is descriptive analysis. The population in this study is the mining sector companies listed on the Indonesia Stock Exchange in 2014-2017, which amounted to 47 companies and the total sample of 36 companies. The analysis technique used is the panel data model test, the classic assumption test, panel data regression analysis, and hypothesis testing using the t-statistical hypothesis test and the F-statistical hypothesis test with a significance level of 5%. The results of the research partially show that leverage has no effect on earnings management, profitability has a positive effect on earnings management, and company size has no effect on earnings management. Simultaneously, leverage, profitability, and company size influence earnings management.